2011
DOI: 10.1177/0269215511412799
|View full text |Cite
|
Sign up to set email alerts
|

Safety and self-reported efficacy of botulinum toxin for adult spasticity in current clinical practice: a prospective observational study

Abstract: Self-reported adverse events following botulinum toxin injections in spasticity are rare, often benign and of short duration in current clinical practice. Botulinum toxin is considered effective by patients in treating spasticity of the upper and lower limbs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 9 publications
(11 reference statements)
0
16
0
3
Order By: Relevance
“…Management of spasticity in HSP using botulinum toxin injections type A (Btx-A) has been described in some studies 4,5,6,7,8 . An injection of Btx-A is considered effective and safe for the treatment of lower limb spasticity in adults 4,6,8,9,10 and children 5 . Some studies have found that, in general, Btx-A combined with physiotherapy improves comfortable gait velocity 4,6,8 in HSP patients, but it is not yet known whether Btx-A improves non-motor manifestations in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Management of spasticity in HSP using botulinum toxin injections type A (Btx-A) has been described in some studies 4,5,6,7,8 . An injection of Btx-A is considered effective and safe for the treatment of lower limb spasticity in adults 4,6,8,9,10 and children 5 . Some studies have found that, in general, Btx-A combined with physiotherapy improves comfortable gait velocity 4,6,8 in HSP patients, but it is not yet known whether Btx-A improves non-motor manifestations in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence-based reviews by the American Academy of Neurology and two international consensus committees came to the conclusion that BoNT is a safe and efficacious treatment for adult spasticity [9][10][11]. Treatmentassociated adverse effects include injection site reactions and muscle weakness, and are usually mild and self-limited if appropriate doses of BoNT are used to treat limb spasticity [12,13].…”
Section: Review Brown Schütz and Simpsonmentioning
confidence: 99%
“…The benefit from BoNT-A is maintained after repeated treatment cycles(66-67) and thus, BoNT-A has been thought to be a first line treatment in focal/multifocal spasticity (68). In addition, BoNT treatment has been shown to improve associated reactions in ULS(69) reduce predetermined disability parameters (including pain) (70)(71)(72)(73), reduce carer burden (70,(73)(74), improve person-centered goals(75) and self-reported efficacy with safety (76). However, efficacy of BoNT-A for improvement of motor control and active functions have not been attained (77).…”
Section: Evidence-based Medicinementioning
confidence: 99%